2020
DOI: 10.1177/0192512120913047
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion in policy contexts. A comparative analysis of domestic energy policies and individual policy preferences in Europe

Abstract: Recent research and real-world processes suggest that effective climate change mitigation policies are not feasible without at least a certain degree of public support. Hence, we investigate the link between existing domestic energy policies and individual policy instrument preferences in 21 European countries. We assume a policy feedback perspective and, thus, start from the idea that the current domestic energy context influences what future policies are possible and preferred by citizens. High political tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 44 publications
0
22
6
Order By: Relevance
“…Thus, the scale was the following: 1 = Strongly against, 2 = Somewhat against, 3 = Neither in favour nor against, 4 = Somewhat in favour, and 5 = Strongly in favour. The fivepoint hedonic scale in question has been used in several earlier studies (e.g., Fairbrother et al, 2019;Stadelmann-Steffen & Eder, 2020;Welsch, 2020). Table 1 shows the descriptive statistics of the dependent variable.…”
Section: Datamentioning
confidence: 99%
“…Thus, the scale was the following: 1 = Strongly against, 2 = Somewhat against, 3 = Neither in favour nor against, 4 = Somewhat in favour, and 5 = Strongly in favour. The fivepoint hedonic scale in question has been used in several earlier studies (e.g., Fairbrother et al, 2019;Stadelmann-Steffen & Eder, 2020;Welsch, 2020). Table 1 shows the descriptive statistics of the dependent variable.…”
Section: Datamentioning
confidence: 99%
“…In this regard, political parties as the organizations that supply members of government and parliament are in a critical position to mitigate the attempts by organized interests to influence climate policy and therefore parties' positions on climate policy warrant enhanced attention (see Carter and Little, 2020). Since research in comparative politics has shown that political parties respond to their electorates when adopting positions on policy issues, the public and its perception of climate change is also an important determinant of the policy responses adopted (see Stadelmann-Steffen and Eder, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Within the USA, California is the leading state in climate policy but some cities and municipalities have adopted even more ambitious climate policies at the local level (Homsy, 2018). This finding also points to the importance of electoral politics (Carter and Little, 2020), media coverage (Yagodin, 2020), and public opinion (Stadelmann-Steffen and Eder, 2020), with ‘green’ voters concentrated in some states such as California and in affluent cities, while other areas of the USA are dominated by voters less supportive of ambitious climate policies (Stokes and Warshaw, 2017).…”
Section: Rationale For the Country-comparative Approachmentioning
confidence: 94%
“…To understand the diversity of factors influencing preferences for coastal adaptation, we look to related bodies of research for insights. These related bodies of research include preferences for mitigation policies [44,45], adaptation in non-coastal settings [37,[46][47][48][49][50], or perceptions and preferences as they relate to household adaptive action [41,[51][52][53][54][55]. According to this research, several factors have been associated with preferences, support, and adaptive behaviours.…”
Section: State Of the Research On Societal Preferences For Coastal Adaptationmentioning
confidence: 93%